Urgensi Dan Signifikansi Pendidikan Islam Berwawasan Multikultural - Yamani, Mohamad Tulus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Multicultural Approach in Islamic Education is necessity. It is a paradigm and method to digs various potential of ethnic and cultural of nation, and embodies in an appropriate conflict management. Multicultural Approach in Islamic Education is wisdom to responding and anticipating the negative impact of globalization that coercing the homogenization and hegemony of patterns and lifestyle. Through Multicultural Approach, Islamic education is expected able to transform inclusifism value so student have open minded about nation that appreciate the diversityof Indonesia.keywords: Islamic Education, Multicultural.